Prevalence and contributing factors of low back pain among nurses at tertiary level hospital in Kathmandu. - Thapaliya, Subekshya (2020)
ABSTRACT: Nursing is a profession with high incidence and prevalence of low back pain (LBP) with its medical and professional consequences. These prevalence rates vary among countries, and with various measurements have been used to determine low back pain. Personal and work-related factors are regarded as causal factors for back pain. The aim of study was to find out the prevalence and contributing factors of LBP among nurses working at a Tertiary level Hospital in Kathmandu. A cross- sectional study was conducted among 290 nurses from different units/ wards at Tribhuvan University Teaching Hospital (TUTH). A self-administered, modified Nordic questionnaire and Keele Start Back Screening were use to collect data regarding prevalence of LBP, its risk status and contributing factors. Descriptive statistics, inferential and univariate logistic regression techniques were used for analysis. The findings of this study broadly confirm the high levels of back pain in nursing, with a one-year prevalence of LBP of 84.1% for LBP of at least one day and 21.92% among them were at high risk status. More than half (63.11%) of nurses reported from being prevented of carrying out normal activities. There was a significant association between LBP and Age; 51-60 yrs (p= 0.041)Body Mass Index; Over weight (p= 0.028) and place of work ; critical care unit (p= 0.023). The prevalence of LBP among nurses at TUTH is high and should be actively addressed. Preventive measures should be taken to reduce the risk of lower back pain, such as implementing ergonomics at work place, educational programs to teach the proper use of body mechanics. Keywords: Low Back Pain, Nurses, Prevalence and contributing Factors.